CROSS-SECTIONAL ANALYSIS OF XIPHISTERNUM FUSION PATTERNS FOR AGE ESTIMATION USING RADIOLOGICAL TECHNIQUES - Dr Sourabh Jyoti Gogoi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Age estimation is crucial in forensic and medico-legal contexts. This cross-sectional study evaluated the utility of radiological assessment of xiphisternum fusion for age estimation in individuals aged 31-45 years. Radiographs were analyzed to determine the presence or absence of complete fusion of the xiphisternum joint. The study found that 63% of participants exhibited fusion, with a slightly higher occurrence in females (33%) than males (30%). The mean age of fusion was 40.05±4.89 years in males and 40.95±3.87 years in females, while non-fusion occurred at a mean age of 35.83±3.38 years in males and 33.30±3.09 years in females. Statistical analysis revealed no significant difference in fusion rates between genders (Chi-Square = 0.287, p = 0.592). The findings indicate that xiphisternum fusion can be a supplementary tool for age estimation, though its reliability requires further investigation.